1993
DOI: 10.1017/s0022215100122170
|View full text |Cite
|
Sign up to set email alerts
|

Penicillamine-induced changes in elastic tissue of the upper respiratory tract

Abstract: We describe a patient who developed upper respiratory tract symptoms following long-term treatment of Wilson's disease with penicillamine. These symptoms were attributed to areas of pharyngeal thickening and were treated with a laser. Histological examination of the lesions showed proliferations of abnormal elastic fibres similar to those previously described at other sites, especially the skin, in patients receiving penicillamine. This drug impairs the maturation and reduces the stability of elastic fibres an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
1
2
1
Order By: Relevance
“…At concentrations above 1000 U/ml, the specificity of the CA19-9 assay is reportedly more than 99% for malignant gastrointestinal disease. 7 The present patient had evidence of neither CA19-9 producing tumours nor obstructive jaundice. Liver biopsy specimen showed severe necrosis in the hepatic lobes and large numbers of proliferated bile ductules.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…At concentrations above 1000 U/ml, the specificity of the CA19-9 assay is reportedly more than 99% for malignant gastrointestinal disease. 7 The present patient had evidence of neither CA19-9 producing tumours nor obstructive jaundice. Liver biopsy specimen showed severe necrosis in the hepatic lobes and large numbers of proliferated bile ductules.…”
Section: Discussioncontrasting
confidence: 54%
“…Over three years, excision biopsies of skin, a gum dermatofibroma, and thickened pharyngeal tissue indicated changes of PPXE. 7 Clinical examination consistently revealed a yellow "plucked chicken" appearance of the folded skin of the neck and axillae but no angioid streaks in the retina. Barium studies showed hold-up to flow through the oesophagus at the cricopharyngeus.…”
Section: Case Reportmentioning
confidence: 97%
“…[4] Long-term d-penicillamine therapy causes multiple degenerative changes in elastic fibers of skin. Similar elastic fiber changes have been reported in upper respiratory tract, [5] pulmonary tissue, [4] aortic wall, visceral adventitia and alveolar septa. [4] Abnormal elastic fibers are not only confined to lesional skin, but also present in non-lesional skin.…”
Section: Discussionsupporting
confidence: 85%
“…3 , 4 These conditions can sometimes occur at the lower dosages used in rheumatoid arthritis. 5 Elastolytic changes may also be seen in other tissues such as the upper respiratory tract, 6 the joint capsules, 7 the lungs, aorta and adventitia of the viscera. 5 The histological feature seen consistently in patients with elastolysis due to penicillamine is ‘lumpy‐bumpy’ 8 or ‘bramble‐bush’ 9 ‐like elastic fibres, which appears to be quite specific.…”
mentioning
confidence: 99%